2009
DOI: 10.1007/s11356-009-0177-6
|View full text |Cite
|
Sign up to set email alerts
|

Farmer knowledge and a priori risk analysis: pre-release evaluation of genetically modified Roundup Ready wheat across the Canadian prairies

Abstract: Farmer knowledge systems are holistic in nature, incorporating socioeconomic, cultural, political, and agroecological factors that all can contribute meaningfully to the pre-release evaluation of GM crops. The inclusion of farmers and other stakeholders in risk assessment will also help enhance and even restore public confidence in science-focused approaches to risk assessment. Although farmers are highly knowledgeable regarding RRW and arguably any agricultural technology, their expertise continues to be over… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
27
0
1

Year Published

2009
2009
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 26 publications
(28 citation statements)
references
References 30 publications
0
27
0
1
Order By: Relevance
“…Studies have found that organic farmers reject the use of GM crops [58], and organic and conventional farmers' resistance to GM crops is well aligned with consumers' views [59]. For instance, Canadian farmers (from organic to GM producers) all ranked the risks associated with herbicide-tolerant wheat (Triticum aestivum) as higher than the benefits [60], a pattern confirmed elsewhere [61,62]. In Austria, where 11% of all farmers practice organic farming, a restrictive coexistence policy for GM crops has been implemented, driven by both the public and organic farmers [63].…”
Section: Socioeconomic Feasibility: Likely Reactions Of Consumers Andmentioning
confidence: 99%
“…Studies have found that organic farmers reject the use of GM crops [58], and organic and conventional farmers' resistance to GM crops is well aligned with consumers' views [59]. For instance, Canadian farmers (from organic to GM producers) all ranked the risks associated with herbicide-tolerant wheat (Triticum aestivum) as higher than the benefits [60], a pattern confirmed elsewhere [61,62]. In Austria, where 11% of all farmers practice organic farming, a restrictive coexistence policy for GM crops has been implemented, driven by both the public and organic farmers [63].…”
Section: Socioeconomic Feasibility: Likely Reactions Of Consumers Andmentioning
confidence: 99%
“…However, OSR volunteers are increasingly prevalent in cultivated fields (Leeson et al 2002), where the presence of multiple GMHT traits can lead to transgene spread (Hall et al 2000;Beckie et al 2003). Management challenges associated with GMHT volunteers, as well as widespread GM crop cultivation in western Canada, have generated much doubt among farmers regarding GMHT trait containment (Mauro and McLachlan 2008;Mauro et al 2009). Indeed, the presence of unwanted GMHT traits is inevitable in Canadian production systems and agricultural supply chains (Demeke et al 2006).…”
mentioning
confidence: 99%
“…Unlike these studies of practical farming, our focus on farmers' assessments of new technology fall within a small group of studies which look at the knowledge farmers draw on when they engage in more general discussions of policies and the regulation of technology within agriculture. Only a few such studies exist, and they typically address farmers' knowledge either in relation to the assessment of the risks and regulation of genetic technologies (Mauro and McLachlan 2008;Mauro et al 2009;Goven and Morris 2012) or in relation to farmers' decisions to adopt a new technology in their own practice (Kaup 2008).…”
Section: Knowledgementioning
confidence: 99%
“…Only a few such studies exist, and they typically address farmers’ knowledge either in relation to the assessment of the risks and regulation of genetic technologies (Mauro and McLachlan ; Mauro et al . ; Goven and Morris ) or in relation to farmers’ decisions to adopt a new technology in their own practice (Kaup ).…”
Section: Introductionmentioning
confidence: 99%